РАЗВИТИЕ КРЕДИТНОЙ СИСТЕМЫ ОБУЧЕНИЯ В ВЫСШИХ УЧЕБНЫХ ЗАВЕДЕНИЯХ (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article examines key aspects of the development of the credit system of education in higher education institutions. The historical background of its implementation, the specifics of its implementation in the context of the Bologna process, as well as the advantages and problems that arise when adapting educational programs to the credit model are analyzed. The impact of the credit system on increasing student mobility, individualizing educational trajectories and ensuring transparency in assessing academic achievements is noted. Emphasis is placed on the need for methodological and organizational improvement of the system in the context of digitalization of education.